Sejarah awal sastra internet di Indonesia: Dari milis ke majalah daring - Rokib, Mohammad (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The transition from the New Order to the Reformasi period in Indonesia not only reshaped the political landscape but also influenced the emergence of digital literature dynamics. This article examines the early development of internet literature as part of the transformation of literary practices within digital culture. Using a historical method, this study analyzes early digital literary traces through platforms such as mailing lists, blogs, and online literary magazines. The findings show that these platforms not only served as alternative publishing channels but also fostered a participatory ecosystem that redefined the boundaries of literary production and reception. Characteristics such as user interactivity, open discussions, and decentralized distribution became key features of this literary space. This study argues that the formative stage of Indonesian internet literature marked the beginning of a new literary culture, one that was digitally based, community-oriented, and distinct from conventional print culture. These developments contributed significantly to the diversification and democratization of literary expression in contemporary Indonesia.